2021
DOI: 10.9734/jpri/2021/v33i47a33025
|View full text |Cite
|
Sign up to set email alerts
|

Updates in Digoxin Toxicity and Outcome of Management: A Review

Abstract: Cardiac glycosides, including digitalis and digoxin, have long-standing use in clinical practice. Digoxin has a half-life that varies from 36 to 48 hours, which may increase in cases of renal failure. Approximately 1% of Congestive Heart Failure patients treated with digoxin develop toxicity. The clinical features of toxicity are often non-specific. Diagnosis is difficult and usually made clinically, as levels of digoxin in the blood do not necessarily correlate with toxicity. Treatment involves early recognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
1
0
0
1
Order By: Relevance
“…Concerning BUN, there were statistically significant differences in pre- and post-digoxin intake, which is consistent with the findings of Ibrahim et al The study found no statistically significant differences in serum albumin levels before and after digoxin intake [ 10 ]. Shen et al had similar findings, with a significant relationship between digoxin intake and serum albumin [ 7 ].…”
Section: Discussionsupporting
confidence: 90%
“…Concerning BUN, there were statistically significant differences in pre- and post-digoxin intake, which is consistent with the findings of Ibrahim et al The study found no statistically significant differences in serum albumin levels before and after digoxin intake [ 10 ]. Shen et al had similar findings, with a significant relationship between digoxin intake and serum albumin [ 7 ].…”
Section: Discussionsupporting
confidence: 90%
“…Konjestif kalp hastalıklarında sıkça kullanılan digoksin terapötik aralığı dar olması sebebiyle intoksikasyonlara sebep olabilmektedir. Digoksin, kardiyak glikozitler olarak adlandırılan ilaç kategorisine ait bir ilaç maddesidir ve dijital glukozidler olarak da adlandırılmaktadır (3). Kardiyak glikozidler de bilinen en eski kardiyak ilaç grubudur (5).…”
Section: Introductionunclassified